Hakikat Manusia dan Daya-Daya Ruhani - Weni, Weni; Muspiarman, Muspiarman; Fadriati, Fadriati; Suryana , Ernis (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research focuses on understanding the nature of humans as God's most perfect creatures, who have a balance between physical and spiritual elements, and how this spiritual dimension plays a role in the development of science. Humans, as creatures with a mind, soul and body, have the potential to achieve good or bad. Through Islamic education, humans are taught to optimize their good potential and control their bad tendencies. This research uses a qualitative approach with literature studies to analyse the views of Ibn Arabi, Ibn Maskawaih, al-Farabi, al-Ghazali, and Ibn Rushd regarding humans as a micro-cosmos, and their influence on the development of science. Apart from that, this research also examines the important role of the spiritual dimension which involves the elements of Ruh, Qalb (heart), Aqal (reason), and Lust in the formation of scientific thinking. The main aim of this research is to explore the relationship between human spiritual potential and science, and how the two can interact positively in improving the quality of human life and society. In this context, the scientific knowledge obtained is not only based on rational logic, but also takes morality and ethics into account in its development.